Dissertation Report on Principal Component Analysis based Approach for Face Recognition - BIBHA MISHRA, SHILPA V RAO, RANJITHA G H and SANTHOSH B L (2006)
INTERNAL GUIDE: A RAMCHANDRAN, MVJCE
Keywords: Principal Component Analysis